Tratamento de caldo e tipos de fermentos sobre os componentes secundários e qualidade da cachaça de alambique - Garcia, Graciany [UNESP] (2016)
Cachaça is the second most widely consumed alcoholic beverage in Brazil, obtained by distillation of sugarcane wine, having its quality affected by the raw material, fermentation conditions and productive process. With the growing demand of the consumer market for quality cachaça, the search for the improvement in relation to the progress of the technical-scientific knowledge has been intensified. The physical chemical treatment of the juice is a technology that qualifies the beverage. This study aimed is to evaluate the performance of two types of yeast (selected CA-11 and the pressed) and the influence of the physical-chemical treatment of sugarcane juice on the secondary compounds and the interference of the same in the quality of the beverage. The experiment was carried out in 2014/2015, using a variety of SP83-2847 cane grown in Pitangueiras-SP region. The trial design was done in blocks with 9 repetitions, 3 cycles with 3 repetitions, where the primary treatment was the clarified juice and not clarified and secondary the two types of yeast. It has assessed the viability of the cells and shoots and the index of budding along the fermentation. In the wine was determined the total acidity, pH, ARRT, alcoholic content, glycerol, efficiency fermentative and mineral composition. In distillates was analyzed total aldehydes, volatile acidity, total esters, methanol, acrolein, ethyl carbamate, furfuraldehyde and hydroxymethylfurfural, higher alcohols, alcohol sec. butyl and n-butanol, all determined by GC and HPLC. The use of CA-11 yeast combined with the juice treatment process, has indicated highest cell viability index and lower alcohol concentrations and congeners coefficient higher in relation to others. All results were lower than the limits allowed by Brazilian law. The results obtained suggest that the use of selected strains with the prior treatment of the juice enables better performance of the fermenting yeasts, resulting in distillate with appropriate physico-chemical standards and with quality.